Bully - Polacco, Patricia (New York : G.P. Putnam's Sons, 2012)
Sixth-grade friends Lyla and Jamie, both new to their school, stand up for each other when a clique of popular girls bullies them online.
School Library Journal, August 2012
Publisher's Weekly, August 2012
4.6
3-6
Keywords: Friendship -- Juvenile fiction; Cyberbullying -- Juvenile fiction; Bullying -- Juvenile fiction; Popularity -- Juvenile fiction; Schools -- Juvenile fiction; Friendship -- Fiction; Cyberbullying -- Fiction; Bullies -- Fiction; Popularity -- Fiction; Schools -- Fiction; Friendship -- Fiction; Cyberbullying -- Fiction; Bullies -- Fiction; Popularity -- Fiction; School stories